Fostering Student Techno-Entrepreneurship: A Qualitative Study Of Universities' Role And Support - Astri Ayu Purwati; Zulfadli Hamzah; Siti Intan Nurdiana Wong Abdullah (International Journal of Information System and Innovation Management (IJISIM), 2023)
This research aims to understand how universities support students in technology-based entrepreneurial ventures. Through a series of interviews, the research identified several key ways in which universities support entrepreneurs, including a proactive approach in promoting entrepreneurship, providing entrepreneurship education and training, providing access to financial resources, and assisting students in networking and securing mentorship. However, the research also uncovered some challenges and barriers, including less rapid response to challenges and a lack of specialized support for technology-based start-ups. This research shows that while universities play an important role in supporting tech-based student entrepreneurship, there is still room for improvement. Further research is needed to understand how universities can design and implement more effective entrepreneurship initiatives, how entrepreneurship education can be more effective in increasing entrepreneurial intentions and skills, how universities can be more effective in supporting the financial aspects of entrepreneurship, and how networking and mentorship can be better utilized in the context of technology-based entrepreneurship.